2014
DOI: 10.1128/aem.03478-13
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Institute Evaluations of Inhibitor-Resistant PCR Reagents for Direct Testing of Aerosol and Blood Samples Containing Biological Warfare Agent DNA

Abstract: The down-selected reagents underwent further testing. In the United Kingdom experiments, both reagents were tested against seven contrived aerosol collector samples containing B. anthracis Ames DNA and B. subtilis spores from a commercial formulation (BioBall). In PCR assays with reaction mixtures containing 40% crude sample, an airfield-collected sample induced inhibition of the B. subtilis PCR with the KAPA reagent and complete failure of both PCRs with the Fast Virus reagent. However, both reagents allowed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…These experiments also demonstrated that the PCR DNA yield decreased when the amount of extract was higher than 2.4 μl. In line with previous interpretation for experiments carried out on environmental samples [24–27], we concluded that the DNA extracts contained PCR inhibitors and we used limited amounts of the DNA extracts in subsequent experiments.…”
Section: Methodssupporting
confidence: 78%
“…These experiments also demonstrated that the PCR DNA yield decreased when the amount of extract was higher than 2.4 μl. In line with previous interpretation for experiments carried out on environmental samples [24–27], we concluded that the DNA extracts contained PCR inhibitors and we used limited amounts of the DNA extracts in subsequent experiments.…”
Section: Methodssupporting
confidence: 78%
“…Although FilmArray control PCRs performed on the discrepant sample were successful, the performance of these assays is measured by the system using only qualitative melt-curve data (5); therefore, an increase in the control PCR C q value, which might indicate a general inhibition effect and therefore explain the EBOV negative, would not be detected by the system. Individual PCRs are known to be differentially affected by the same inhibitor (16), supporting the hypothesis of a control PCR success but EBOV PCR failure.…”
supporting
confidence: 56%
“…The PCR is dependent on used primers, which are responsible for the specificity of the method. Various configurations of the method are available from which real time PCR is likely the most widely used in the current praxis [16,17]. There are also commercially available PCR devices suitable for field assay.…”
Section: Expected Use Of Biosensors During a Biological Threatmentioning
confidence: 99%